Instability of dilative sand - Chu, J.; Wanatowski, D.; Leong, W.K.; Loke, W.L.; He, J. (Thomas Telford (ICE Publishing), 2015)
A type of pre-failure instability which occurs for medium loose to dense sand under fully drained conditions is studied in this paper. It is observed experimentally that when a specimen is sheared along a drained stress path involving a decrease in the effective mean stress, it becomes unstable after the stress path crosses an instability line. The instability line specifies a minimum stress ratio under which instability may occur. It is not unique, but changes with the void ratio of the soil and the applied effective stresses. The instability occurring under drained conditions is different from that under undrained conditions. The differences and similarities between the two types of instability are pointed out. Practical implications of the study in analysing the failure mechanisms of granular soil slopes under various drainage conditions are discussed.